2015
DOI: 10.1097/mph.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Successful T-cell–depleted Haploidentical Hematopoietic Stem Cell Transplantation in a Child With Dyskeratosis Congenita After a Fludarabine-based Conditioning Regimen

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the only cure for marrow failure associated with dyskeratosis congenita (DC). Data on transplants from alternative donors are limited. We describe a boy with DC and severe aplastic anemia who underwent haploidentical T-cell depleted HSCT using a reduced-intensity conditioning regimen. He underwent engraftment without toxicity or GVHD. His posttransplant course was complicated by EBV reactivation, treated with rituximab and EBV-specific T lymphocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A nonradiation regimen with fludarabine, lower-dose melphalan, and alemtuzumab resulted in 5 of 7 patients alive in early follow-up [76]. There has also been success in the haploidentical setting with a similar RIC approach and the use of ex vivo T cell depletion [77]. …”
Section: DCmentioning
confidence: 99%
“…A nonradiation regimen with fludarabine, lower-dose melphalan, and alemtuzumab resulted in 5 of 7 patients alive in early follow-up [76]. There has also been success in the haploidentical setting with a similar RIC approach and the use of ex vivo T cell depletion [77]. …”
Section: DCmentioning
confidence: 99%
“…2 Several reports have shown that despite being a bone marrow failure syndrome, the use of reduced intensity conditioning preparative regimens are safer, carries less morbidity and has no increased risk of graft failure or rejection. 1,8,[9][10][11][12][13] In some of these reports, however, the ex vivo T-cell depletion was with ATG and in general, the source of stem cells was nonumbilical cord blood stem cells. In both patients in this report, ATG was replaced with alemtuzumab, which has more in-depth lymphocyte depletion with the hope that this will decrease any chance for rejection.…”
Section: Patientmentioning
confidence: 99%
“…[5][6][7][8] Combination of RIC with T-cell depletion from grafts raises the concerns of non-engraftment but successful CD34 + cell selected haploidentical transplant has been recently reported. 9 Novel ex vivo T-cell depletion techniques using TCR αβ and CD19 depletion have many potential advantages. Removal of αβ-T cells by 4-5 logs can reduce the risk of GvHD but at the same time facilitates excellent CD34 + cell recovery while retaining γδ T cells, dendritic cells, natural killer (NK) cells and monocyte/myeloid cells, thereby ensuring early robust engraftment and immune reconstitution.…”
mentioning
confidence: 99%